2015
DOI: 10.1021/nl502227a
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nanowire-Induced Maturation of Cardiomyocytes Derived from Human Induced Pluripotent Stem Cells

Abstract: The current inability to derive mature cardiomyocytes from human pluripotent stem cells has been the limiting step for transitioning this powerful technology into clinical therapies. To address this, scaffold-based tissue engineering approaches have been utilized to mimic heart development in vitro and promote maturation of cardiomyocytes derived from human pluripotent stem cells. While scaffolds can provide 3D microenvironments, current scaffolds lack the matched physical/chemical/biological properties of nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 39 publications
1
72
0
1
Order By: Relevance
“…Recently, nanocomposite scaffolds composed of conductive nanowires were confirmed to enhance the maturation of CMs derived from stem cells with a significantly improved sarcomere length and Z-line width. 21 Besides the 26,27,35,36 Our data here also convincingly demonstrate that CNTs enhance the maturation of CMs with higher sarcomere length and greater assembly of gap junctions between adjacent CMs derived from BASCs.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Recently, nanocomposite scaffolds composed of conductive nanowires were confirmed to enhance the maturation of CMs derived from stem cells with a significantly improved sarcomere length and Z-line width. 21 Besides the 26,27,35,36 Our data here also convincingly demonstrate that CNTs enhance the maturation of CMs with higher sarcomere length and greater assembly of gap junctions between adjacent CMs derived from BASCs.…”
Section: Discussionsupporting
confidence: 77%
“…20 Different striation regions of ten cells were calculated using ImageJ software. Z-line width was also assessed using ImageJ software according to a previous study, 21 and ten Îą-SA+ cells were measured with ten measurements for each cell. TgF-β1 bioassay TGF-β1 levels in BASCs grown on the scaffolds were quantified using a commercially available ELISA kit (TGF-β1 Emax ÂŽ ImmunoAssay System; Promega, Madison, WI, USA) according to the protocol provided by the manufacturer.…”
Section: Assay Of Sarcomere Length and Z-line Widthmentioning
confidence: 99%
“…Previous work using hiPSC-CM spheroids has indicated conditioning approaches and extended culture are required to enhance the contractile properties toward physiological relevance (14, 79). We next explored the effect of cellular and matrix microenvironment as a biomimetic stimulus in the organoids to promote the contractile properties of hiPSC-CM.…”
Section: Resultsmentioning
confidence: 99%
“…As described in our previous publication (79), the agarose hydrogel molds were prepared using 2% agarose (Sigma Aldrich, St. Louis, MO) and master micro-molds from Microtissues, Inc (Providence, RI) as negative replicates to create non-adhesive agarose hydrogels molds containing 35 microwells with hemispheric bottoms (800 Îźm diameter, 800 Îźm deep) to facilitate the formation of spherical microtissues. Molds were soaked in cell/organoid specific media prior to microtissue fabrication.…”
Section: Methodsmentioning
confidence: 99%
“…25 Likewise, electrical nanomaterials have provided an endogenous means of improving electrical conductivities of cardiac microtissues. 29–31 We have previously shown that the addition of electrically conductive silicon nanowires (e-SiNWs), a class of biodegradable nanomaterials, 32 into scaffold-free 3D cardiac spheroids creates an electrically conductive microenvironment and leads to advancement in the function and structural development of hiPSC-CMs. 31 …”
mentioning
confidence: 99%